Sifat Fisikokimia dan Sensoris Brownies Kukus Mocaf Berdasarkan Perbandingan Margarin dan Puree Alpukat - Pardosi, Tatia Hanauli; Arihantana, Ni Made Indri Hapsari; Putra, I Gede Arie Mahendra (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 4 (2024): Jurnal ITEPA, 2024)
Steamed MOCAF brownies are chocolate flavoured cakes that has a soft texture and sweet taste made by steaming and made from local gluten free flour. Main ingredient in making steamed MOCAF brownies is margarine, but high consumotion of margarin can caused negative effects on health, therefore, avocado which contains high levels of monounsaturated fatty acids can served as a healthier fat substitute. The purpose of this research was to determine the comparison between margarine and avocado puree on the physicochemical and sensory qualities of steamed MOCAF brownies and to determine the correct ratio for producing products with the best characteristics. Five different ratios of margarine and avocado puree (100:0, 85:15, 70:30, 55:45, and 40:60) were tested using Completely Randomized Design (CRD) and each treatments were repeated three times to obtain a total of 15 observation objects. The data were examine using variance, subsequently subjected to Duncan’s Multiple Range Test (DMRT). The outcomes showed that the subtitution of margarine with avocado puree had a significant effect on water content, fat content, free fatty acid, iodine value, hardness level, texture and taste. Steamed MOCAF brownies with the best characteristics were obtained by the comparison of 55 percent margarine and 45 percent avocado puree with the results of water content 34.07 percent, fat content 23.62 percent, free fatty acid 0.833 percent, iodine value 58.4 percent, hardness level 3.86 N with the color, aroma, and texture were very much liked, taste was slightly bitter and liked, and the overall acceptance was very liked. Keywords: steamed brownies, mocaf, avocado puree, margarine, physicochemical